Colossal dielectric response and relaxation properties in Co2Z-type hexaferrites. Issue 15 (15th October 2017) - Li, C.L.; Huang, S.; Chen, X.H.; Yan, T.Y.; Fu, Q.S.; Zhang, R.; Zhu, C.M.; Yuan, S.L.
Abstract: Polycrystalline samples of Sr3 Co2 Fe24 O41 and Ba3 Co2 Fe24 O41 have been prepared by a sol-gel method. The XRD data indicate that the samples are Co2 Z-type hexaferrites with the centrosymmetric space group of P6 3 /mmc . The SEM micrographs suggest that mixture plate-like grains are formed and Sr3 Co2 Fe24 O41 shows more dense grain structure. High-temperature dielectric relaxation behaviors are studied in a wide range of frequency and temperature through dielectric and impedance spectroscopies analysis. Colossal dielectric permittivity is observed at low frequency and dielectric relaxation behavior is clearly seen at high temperatures. Two types of relaxations are observed in Sr3 Co2 Fe24 O41 and it is attributed to the thermally activated model which follows the Arrhenius law. The X-ray photoelectron spectroscopy indicates that Fe 2+ and Fe 3+ coexist in the system and the dielectric relaxations originate from the carriers hopping between Fe 2+ and Fe 3+ . Moreover, the high concentration of Fe 2+ in Ba3 Co2 Fe24 O41 causes the high dielectric permittivity at low frequency range and the relatively low conductivity at high temperature.